1992
DOI: 10.1128/jvi.66.4.1995-1999.1992
|View full text |Cite
|
Sign up to set email alerts
|

v-Src enhances phosphorylation at Ser-282 of the Rous sarcoma virus integrase

Abstract: The Rous sarcoma virus (RSV) integrase (IN) and the 13 polypeptide (13) of the reverse transcriptase are posttranslationally modified by phosphorylation on Ser at amino acid position 282 of IN. When IN was immunoprecipitated from RSV (Prague A strain) virions, approximately 30 to 40%o of the IN molecules were phosphorylated. When IN was immunoprecipitated from a v-src deletion mutant (AMst-A) of RSV or from avian myeloblastosis virus (AMV), the percentage of IN molecules that were phosphorylated was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further natural partial proteolytic processing of the IN tail region results in approximately 5-6 residues being removed from its C termi- nus, which does not grossly affect replication of the virus; partial phosphorylation of RSV IN at Ser-282 in vivo (Fig. 1) prevents proteolytic processing of the tail region at the very C terminus (20,21,43). Mutagenesis studies both in vitro and in vivo of the ␤-strand region of the SH3 domain in RSV IN showed that this region is essential for virus replication and concerted integration (13,15,20,46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further natural partial proteolytic processing of the IN tail region results in approximately 5-6 residues being removed from its C termi- nus, which does not grossly affect replication of the virus; partial phosphorylation of RSV IN at Ser-282 in vivo (Fig. 1) prevents proteolytic processing of the tail region at the very C terminus (20,21,43). Mutagenesis studies both in vitro and in vivo of the ␤-strand region of the SH3 domain in RSV IN showed that this region is essential for virus replication and concerted integration (13,15,20,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The cleaved 37-amino acid polypeptide, whose function is unknown, is not essential for virus replication (19). Approximately 5-6 residues at the C-terminal end of RSV IN (amino acids 1-286) are also not essential for replication (20,21). There are also 10 -12 residues at the very C terminus of the tail region of human immunodeficiency virus type 1 (HIV-1) IN (amino acids 1-288) that are not critical for virus replication but nonetheless enhance the functions of IN with increasing efficiency in accordance with its length (22,23).…”
mentioning
confidence: 99%
“…AMV IN is a dimer in solution as determined by velocity sedimentation (14) or by chemical cross-linking studies with disuccinimidyl suberate (DSS) and as determined by denaturing SDS-polyacrylamide gel electrophoresis. AMV IN exists as two polypeptides upon reducing SDS-polyacrylamide gel electrophoresis: one minor full-length polypeptide (286 amino acids) and one major slightly truncated polypeptide (approximately 282 amino acids) at its carboxyl terminus (26). Treatment of IN in the range of 0.32 to 2.2 ,uM with DSS (2 mM) or varying the DSS concentration (0.01 to 2 mM) with IN at 2.2 ,uM resulted in the formation of two B separate cross-linked polypeptide chains with molecular weights of 62,000 and 64,000 upon reducing SDS-polyacrylamide gel electrophoresis (38).…”
Section: Fig 2 Mapping the Location And Frequency Of In Bound Tomentioning
confidence: 99%